Calibration of Dynamic Line Rating Model for Phasor Measurement Unit Based Wide Area Measurement System in Smart Grid Application - Mohammad Kamrul, Hasan; Musse, Mohamud Ahmed; Sherfriz Sherry, Musa; Denis, Lee (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The inefficiency of power transmission lines always becoming an issue in power system analysis. One of the most applicable methods Dynamic Thermal Current Rating (DTCR) to measure the thermal line ratings of existing transmission lines. This DTCR system operated through Phasor Measurement Units (PMUs) in Wide Area Measurement (WAM) system of the Sarawak Energy. To calculate the line rating based on measured or predicted weather conditions of the overhead transmission lines. However, the existing DTCR system of Sarawak Energy facing several accuracy issues. Therefore, this paper intended to perform an extended study on the sensitivity analysis of conductors in overhead transmission lines using the dynamic thermal rating model. The parameters (wind speed, the density of air, solar radiation) that influence the thermal line ratings considered in measuring, assessing the conductors’ thermal effects and then these parameters were considered for the line rating models that dynamically will adjust the weather information of the conductor in overhead transmission lines on WAM systems. The performance of this study carried out using Matlab based simulation. The result shows that the proposed model that uses the dynamic factors brings the expected outcome in measuring the accurate ratings of the overhead transmission lines.